2018
DOI: 10.17576/gema-2018-1802-08
|View full text |Cite
|
Sign up to set email alerts
|

Procedures in the Translation of Proper Names in Harry Potter and the Goblet of Fire into Malay

Abstract: In fantasy fiction, names play a fundamental role in portraying the characters' personality traits and identity. Names are also sometimes chosen to create certain effects. The fact that names may carry meaning raises the question of how names are dealt with in translation. This issue is especially pertinent in the case of the Harry Potter novels in which many of the names have associative meanings. In view of this, the aim of this study is to determine the procedures used in the translation of some of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This could have been due to misinterpretations of the SL items, or a lack of knowledge with respect to the SL history and culture. Therefore, recognizing an idiomatic expression (or even names, as observed by Zabir and Haroon, 2018) and understanding its cultural backdrop or the implications behind, and circumstances surrounding, it will only serve to assist the translator in terms of accurate rendition as well as successful transfer of cultural knowledge where applicable.…”
Section: Discussionmentioning
confidence: 99%
“…This could have been due to misinterpretations of the SL items, or a lack of knowledge with respect to the SL history and culture. Therefore, recognizing an idiomatic expression (or even names, as observed by Zabir and Haroon, 2018) and understanding its cultural backdrop or the implications behind, and circumstances surrounding, it will only serve to assist the translator in terms of accurate rendition as well as successful transfer of cultural knowledge where applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the previous studies (Zabir and Haroon, 2018;Eriko, 2016;Majed and Bakri, 2014;Isaiah, 2009, Mussche andWillems, 2010;Nazarabadi and Ghareghani, 2016) showed how proper names in a particular language or country were translated into other languages. It is showed that the proper name is important to be translated.…”
Section: Introductionmentioning
confidence: 93%
“…The issue of translation strategies is dominantly related to the issue of translation procedures (Suryawinata & Hariyanto, 2016, p. 67). The previous study on the translation procedures has been conducted by (Zabir & Haroon, 2018) related to the procedures of proper name translation in the book of Harry Potter and the Gable into Malay. This research main focus is the "translation loss".…”
Section: Literature Reviewmentioning
confidence: 99%